Does The Dividend Policy Affect the Stock Price? - I Komang Oka Permadi; I Kadek Bagiana; Putu Ayu Diah Widari Putri (AIBPM Publisher, 2022)
Stock prices have long been a fascinating topic for researchers, especially in the financial industry, in this digital era. Stock price fluctuations are caused by a variety of variables, one of which is corporate dividend distribution. Dividends are not only a source of income for investors, but they also serve as a barometer of a company's performance. Companies with a bigger market capitalization are better equipped to pay dividends than companies with a smaller market capitalization, hence this will affect the stock price. With firm size as the moderating variable, the point of this study is to re-examine and affirm the impact of dividend policy on stock prices. In this study, the population is manufacturing enterprises that listed on the Indonesia Stock Exchange in 2020. The sample was determined using a non-probability method and purposive sampling technique, and a total of 72 companies were collected. Path analysis is the analytical technique utilized. The findings of this study show that dividend policy has a positive impact on stock prices, and that firm size has no effect on dividend policy's impact on stock prices.Â Keywords: dividend policy, stock price, firm size, manufacturing company.